Mnemotecnias como estrategia metodológica en Química General (Tabla periódica y sus propiedades periódicas) con estudiantes de segundo semestre de la Carrera de Pedagogía de las Ciencias Experimentales Química y Biología, periodo octubre 2021 - marzo 2022 - Caguana Granizo, Katherine Mishell (2022)
One of the biggest challenges that students have faced during the study of chemistry has been the low retention of the information of the periodic table and its periodic properties, generating demotivation and complications in their learning, for this reason, the objective of the study was directed to propose mnemonics as a methodological strategy in General Chemistry for the learning of the periodic table and its periodic properties. A quantitative approach methodology was used, with a non-experimental design; the type of research was descriptive, bibliographic, and field research; and we worked with a population of 36 second semester students of the Pedagogy of Experimental Sciences in Chemistry and Biology, to whom the survey technique was applied through a questionnaire. After analyzing the results, it was concluded that mnemonics as a methodological strategy does contribute to the significant learning of General Chemistry, considering that acrostics, the Loci technique, the association of memories and images, help the appropriation of basic concepts for the study of the periodic table and its properties. Therefore, their use was recommended to support the learning process of these contents.